Foamed nickel-loaded basic nitrate catalytic material, preparation method and application of foamed nickel-loaded basic nitrate catalytic material in seawater electrolysis

The polymetallic alkaline nitrate catalyst supported by foam nickel is prepared by hydrothermal method, NO3-acid ions and a second metal such as Fe are introduced to form a regular nanosheet or nanolayer structure, which solves the problems of insufficient selectivity, poor corrosion resistance and low stability in seawater electrolysis, and achieves efficient and stable OER catalytic performance.

CN119913543APending Publication Date: 2025-05-02XI AN JIAOTONG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510084819.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing OER catalysts have problems such as insufficient selectivity, poor corrosion resistance and low stability in seawater electrolysis, especially in high concentrations of Cl-environment, which leads to low catalytic efficiency and environmental pollution.

Method used

The foamed nickel-supported polymetallic basic nitrate catalyst is prepared by hydrothermal method, and NO3-acid ions and a second metal such as Fe are introduced to form a regular nanosheet or nanolayer structure to improve catalytic activity and stability.

Benefits of technology

It has excellent OER selectivity and corrosion resistance in seawater electrolysis, reduces the overpotential and improves the stability and service life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913543A_ABST
    Figure CN119913543A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of catalytic materials, and discloses a preparation method of an alkaline nitrate catalytic material (Fe-NiNH / NF) and application of the alkaline nitrate catalytic material in electrocatalytic oxygen evolution reaction in seawater. The basic nitrate catalyst is innovatively prepared by designing basic nitrate and optimizing a hydrothermal method preparation process, and the catalyst forms a regular nanosheet or nanolayer structure and can uniformly cover a three-dimensional porous substrate of foamed nickel. The sheet structure not only significantly increases the surface area, but also provides more active sites for the reaction, thereby greatly improving the OER catalytic efficiency. Meanwhile, NO3-acid radicals are introduced, and the acid radical ions can effectively regulate and control electron distribution in the structure and have a stabilizing effect on real active species in the catalysis process. In addition, the preparation process provided by the invention realizes relative simplification on the core steps of pretreatment of the foamed nickel, multi-metal basic salt loading by a hydrothermal method, metal synergistic doping hydrothermal reaction and the like, and is suitable for industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalytic materials, and in particular to a foamed nickel-loaded basic nitrate catalytic material, a preparation method thereof, and application thereof in electrolysis of seawater. Background Art

[0002] Among many renewable energy sources, hydrogen (H2) is an ideal alternative to traditional fossil fuels due to its high energy density and pollution-free nature. Electrocatalytic water splitting is a green and environmentally friendly method for preparing H2. However, in the two half reactions of electrocatalytic water splitting, the oxygen evolution reaction (OER) occurring at the anode involves a slow four-electron transfer process and thus has a high energy barrier, which is considered to be the bottleneck limiting the overall efficiency of electrocatalytic water splitting.

[0003] Conventional water electrolysis to produce hydrogen uses fresh water as the electrolyte. However, due to population growth and increasing water pollution, fresh water is becoming a limited resource worldwide. In contrast, seawater, which accounts for 96.5% of the world's water reserves, is an almost inexhaustible resource. However, seawater is rich in Cl - , using seawater as the electrolyte, ClOR reaction may also occur at the same time as OER reaction. In the process of seawater electrolysis, chlorine formed under acidic conditions and hypochlorite produced under alkaline conditions are both dangerous and difficult to handle. Therefore, ClOR is not desirable in seawater electrolysis, and seawater splitting needs to be controlled to make it completely OER selective. In addition, high concentrations of corrosive Cl in seawater - Strong corrosion to OER catalysts, especially to transition metal-based materials. Therefore, catalysts used for seawater OER must not only have excellent OER selectivity, but also excellent Cl resistance. - Corrosive.

[0004] The current mainstream OER catalysts include precious metal-based and non-precious metal-based materials. Among them, Ru / Ir-based catalysts are widely studied due to their excellent performance. For example, commercial IrO2 -2 The corresponding overpotential is 410 mV, which is mainly used in acidic OER (CHEREVKO et al., 2016). Commercial RuO2 has a current density of 100 mA cm -2 When the overpotential is 390 mV (LEE et al., 2012). However, in alkaline seawater, the RuO2 electrode will be affected by Cl - Due to the influence of plasma, side reactions (such as the production of chlorine) occur, resulting in reduced OER selectivity and Faradaic efficiency, which not only wastes electrical energy but may also have an impact on the environment.

[0005] Non-precious metal-based catalysts have received increasing attention in recent years. For example, commercial Co3O4 has a high current density of 100 mA cm -2 The corresponding overpotential is 460 mV (JIN et al., 2023). Commercial NiFe LDH has a current density of 100 mA cm -2 When the overpotential is 310 mV, it is a relatively advanced alkaline water oxidation catalyst, but its activity in alkaline seawater is relatively limited. The poor corrosion resistance has largely hindered the further application of NiFe LDH in seawater electrolysis (YOU et al., 2022).

[0006] Although Ru / Ir-based catalysts are widely regarded as excellent electrocatalysts for OER, their high cost and scarcity hinder their widespread application. As an alternative, nickel foam (Ni foam) as a substrate material has good conductivity, porosity and large specific surface area, and is widely used in catalyst-supported materials. Foamed nickel-based catalytic materials usually use nickel-based compounds such as Ni(OH)2, NiO or NiOOH as the catalytic layer. However, the catalytic activity and stability of single nickel-based catalysts are often limited in the oxygen evolution reaction, and it is difficult to meet the requirements of low overpotential, high efficiency and long-term stability.

[0007] Basic metal salts (such as M(OH) x (A) γ , where A may be F - 、CO3 2- 、NO3 - The structure of nickel foam (such as nickel hydroxide) is similar to that of hydroxide, but because it contains acid ions, these acid ions can regulate the formation and stability of catalytically active species (such as MOOH). Studies have shown that the activity of the OER reaction and the stability of the material can be enhanced by combining basic metal salts with nickel foam. Currently, basic salts of metals such as Ni, Fe, and Co are common catalyst materials in alkaline electrolytes, but there is a lack of systematic research on the effects of different metal doping.

[0008] The hydrothermal method is a low-temperature, low-energy synthesis method that is widely used to prepare nanostructures and porous materials. The hydrothermal method is applied to the synthesis of nickel foam-supported basic salt catalysts, which can achieve uniform loading of metal basic salts on nickel foam under relatively mild conditions. At present, the use of hydrothermal method for Ni-based material loading is relatively common, but there are few studies on the preparation and optimization methods of basic salt materials doped with multiple metals and their effects on material properties.

[0009] In the prior art, Ni-Fe, Ni-Co based hydroxide or oxide catalysts are often used in oxygen evolution reaction (OER). Such catalysts are usually loaded with nickel foam, and the catalytic performance is improved by introducing metal elements such as Fe and Co. However, such catalysts have the following disadvantages:

[0010] First, in terms of structure, the structure of traditional Ni-Fe and Ni-Co catalysts is usually disordered nanoparticles or nanoaggregates attached to the surface of nickel foam; this nanoparticle structure is prone to agglomeration problems, and the active sites are unevenly distributed, which reduces the effective specific surface area of ​​the material and leads to low catalytic efficiency. This problem of particle aggregation limits the effective transmission of electrons and ions in the OER process, thereby affecting the catalytic performance. Secondly, in terms of stability, traditional Ni-Fe and Ni-Co based catalysts usually have a significant decrease in catalytic activity after long-term use due to the gradual degradation of the structure and the peeling of the catalytic layer. In particular, single metal or simple binary metal catalysts are not stable enough under high potential conditions and are prone to oxidation or deactivation. Finally, in terms of conductivity, many existing Ni-based catalysts have low electron transfer efficiency in OER reactions due to their poor conductivity. In particular, the particles or agglomerate structures attached to the porous nickel foam support make the conductivity less than ideal, thereby limiting the catalytic efficiency.

[0011] In the prior art, there are also nickel foam-loaded nanosheet catalysts; such catalysts usually also have a nanolayer structure, thereby improving the OER catalytic activity. However, most of these technologies use hydroxides or oxides (such as Ni(OH)2 or NiOOH) as the catalytic layer, and the material composition is relatively single. Often due to limited specific surface area and uneven distribution of active sites, the catalytic efficiency cannot be further improved. In addition, due to the lack of regulatory effects of acid ions, the generation of active species is insufficient, which in turn affects the OER activity.

[0012] The current technology still has the problem of complex process and high cost. For example, most preparation methods require complex precursors and high-temperature calcination processes, and the doping process is cumbersome and costly, making it difficult to achieve large-scale industrial preparation. There are few studies on the preparation and optimization methods of basic salt materials doped with multiple metals and their effects on material properties. Therefore, the key to promoting the industrialization of seawater electrolysis technology is to develop a catalyst based on reasonable structural design and combined with multi-metal synergistic effects, optimize the preparation process, and reduce manufacturing costs to achieve excellent OER activity, high corrosion resistance and long-term stability.

[0013] References:

[0014] CHEREVKO S,GEIGER S,KASIAN O,et al.,2016.Oxygen and hydrogenevolution reactions on Ru,RuO2,Ir,and IrO2 thin film electrodes in acidic andalkaline electrolytes:A comparative study on activity and stability.CatalysisToday,262:170-180.DOI:10.1016 / j.cattod.2015.08.014.

[0015] JIN D S,WOO H,PRABHAKARAN S,et al.,2023.Single Phase TrimetallicSpinel CoCr x Rh 2-x O4Nanofibers for Highly Efficient Oxygen Evolution Reactionunder Freshwater Mimicking Seawater Conditions.Advanced Functional Materials,33(25).DOI:10.1002 / adfm.202301559.

[0016] LEE Y,SUNTIVICH J,MAY K J,et al.,2012.Synthesis and Activities ofRutile IrO2 and RuO2Nanoparticles for Oxygen Evolution in Acid and AlkalineSolutions.Journal of Physical Chemistry Letters,3(3):399-404.DOI:10.1021 / jz2016507.

[0017] YOU HH,WU DS,SID H,et al.,2022.Monolayer NiIr-Layered DoubleHydroxide as a Long-Lived Efficient Oxygen Evolution Catalyst for SeawaterSplitting.Journal of the American Chemical Society,144(21):9254-9263.DOI:10.1021 / jacs.2c00242. Summary of the invention

[0018] In view of the shortcomings of the prior art, the present invention provides a method for preparing a basic nitrate catalytic material. - 、CO3 2- 、NO3 - The structure of the metal salt is similar to that of the hydroxide, and it contains additional acid anions. The acid anions contained in the metal basic salt will affect the formation of the real active species MOOH, which is expected to further improve the OER activity of the material. The preparation method mainly prepares a variety of basic salt catalysts loaded on nickel foam by hydrothermal method, and introduces a second metal therein. The best catalytic material is determined based on XRD and LSV performance.

[0019] To achieve the above object, the present invention adopts the following technical solutions:

[0020] The first aspect of the present invention provides a basic nitrate catalytic material supported by nickel foam, wherein the basic nitrate catalytic material is an active layer of metal basic nitrate composited on a nickel foam substrate; the metal includes one or more of Ni, Fe, Co and Cu.

[0021] In some embodiments, the active layer of the basic nitrate catalytic material is one or more of Ni(OH)2, NiNH, Fe-NiNH / NF, Co-NiNH / NF or Cu-NiNH / NF.

[0022] In some embodiments, the volume ratio of the nickel foam to the metal ions is (0.5-1.2) cm 3 :5mmol.

[0023] Preferably, the volume ratio of the nickel foam to the metal ions is 0.8 cm 3 :5mmol.

[0024] In some embodiments, when preparing the above-mentioned basic nitrate catalytic material, a Ni precursor compound and a metal nitrate are dissolved in a solvent, and after adding nickel foam, the mixture is obtained by a hydrothermal reaction.

[0025] Furthermore, the above-mentioned Ni precursor compound is Ni(NO3)2·6H2O.

[0026] Furthermore, the metal nitrate is M(NO3) x nH2O; wherein M is one or more of Ni, Fe, Co, and Cu; and x and n are the stoichiometric numbers of nitrate and crystal water, respectively.

[0027] Furthermore, the reaction temperature is 110-130°C and the reaction time is 6-12h.

[0028] In some embodiments, the metal nitrate is Fe(NO3)3·9H2O; the reaction temperature is 120°C; and the reaction time is 12 hours.

[0029] In some embodiments, the usage ratio of the Ni precursor compound and the metal nitrate is 4 mmol:1 mmol.

[0030] The second aspect of the present invention provides a method for preparing a basic nitrate catalytic material supported by nickel foam, comprising the following steps:

[0031] a) pre-treating nickel foam;

[0032] b) 4mmol Ni(NO3)2·6H2O and 1mmol M(NO3) x nH2O is dissolved in anhydrous ethanol; the M is represented by Ni, Fe, Co or Cu, and the x and n are the stoichiometric numbers of nitrate and crystal water, respectively;

[0033] c) adding the pretreated nickel foam to the above solution, transferring it to a hydrothermal reactor, reacting at 110-130° C. for 6-12 hours to obtain a sample;

[0034] The volume ratio of the nickel foam in step a) to the metal in step b) is (0.5-1.2) cm 3 :5mmol;

[0035] d) Wash the sample and dry it in vacuum at 50-70°C.

[0036] The third aspect of the present invention provides the use of the above-mentioned basic nitrate catalytic material or the catalytic material prepared by the above-mentioned preparation method in the field of hydrogen production by anode water electrolysis.

[0037] Furthermore, the hydrogen production by water electrolysis is hydrogen production by seawater electrolysis.

[0038] The Fe-NiNH / NF prepared by the present invention has better electrocatalytic oxygen evolution performance than the original Ni(OH)2. Therefore, in the technical scheme of the invention, Fe-NiNH / NF doped with the second metal Fe is prepared by hydrothermal method, and NO3 in the basic salt is - The introduction of effectively improved the OER activity of Ni(OH)2, while the introduction of Fe further improved its activity, requiring only an overpotential of 310 mV at 100 mA cm-2. At the same time, Fe-NiNH / NF also has fast OER kinetics and excellent stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The following are SEM images of the samples of the embodiments and comparative examples.

[0040] Figure 2 This is the XRD spectrum of Ni(OH)2 / NF.

[0041] Figure 3 XRD diffraction patterns and Raman comparison diagrams of NiNH / NF, Fe-NiNH / NF, Co-NiNH / NF, and Cu-NiNH / NF.

[0042] Figure 4 The XPS diagrams of the examples and comparative samples are used to determine the states of the elements in the catalyst.

[0043] Figure 5 It is the LSV performance test diagram of seawater OER of the embodiment and comparative example samples.

[0044] Figure 6 To test the electrochemical performance of the samples of the embodiments and comparative examples. DETAILED DESCRIPTION

[0045] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as limiting the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.

[0046] In the examples, the test methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used can be purchased from the market or prepared according to conventional methods well known to those skilled in the art unless otherwise specified.

[0047] In view of the shortcomings of the prior art, this application innovatively prepares a basic nitrate catalyst by designing and optimizing the hydrothermal preparation process of basic nitrate (such as Ni(OH)2 / Fe(NO3)3, etc.), which forms a regular nanosheet or nanolayer structure that can be evenly covered on the three-dimensional porous substrate of nickel foam. This sheet structure not only significantly increases the surface area, but also provides more active sites for the reaction, thereby greatly improving the OER catalytic efficiency; at the same time, this application introduces NO3 - Acid radicals, which can effectively regulate the distribution of electrons in the structure, and have a stabilizing effect on the real active species (such as MOOH) in the catalytic process. In addition, the preparation process of the present invention is relatively simplified in the core steps of pretreatment of nickel foam, hydrothermal loading of multi-metal basic salts, and hydrothermal reaction of metal synergistic doping, and is suitable for industrial application.

[0048] The invention provides an anode electrode material for producing hydrogen by electrolyzing seawater, comprising: a foamed nickel substrate and a basic nitrate layer doped with different metals composited on the foamed nickel substrate.

[0049] Wherein, the different metals may be Ni, Fe, Co or Cu.

[0050] According to some embodiments of the present invention, the basic nitrate layer doped with different metals is a regular nanosheet or nanolayer structure, and is evenly covered on the three-dimensional porous substrate of nickel foam. Among them, the nanosheet structure effectively avoids the problem of particle agglomeration, enhances electronic conductivity, and at the same time expands the contact area between the electrolyte and the catalytic material, thereby improving the overall reaction efficiency.

[0051] According to some embodiments of the present invention, the basic nitrate layer doped with different metals is preferably a basic nitrate layer doped with Fe, and the basic nitrate layer doped with Fe is a transition metal hydroxide nanosheet that grows in a vertically staggered manner to form an array layer. The structure has a nanosheet structure with a high specific area, and the introduction of iron elements can enhance the cohesion of the sheet structure to a certain extent, making the nanosheet structure more stable, not easy to peel off and agglomerate, thereby improving the mechanical strength and long-term stability of the sheet structure.

[0052] According to some embodiments of the present invention, NO3 is introduced by designing basic nitrates (such as Ni(OH)2 / Fe(NO3)3, etc.). - Acid radical, unlike ordinary hydroxide, this basic nitrate structure has higher activity. Acid radical ion NO3 - It can regulate electron distribution and stabilize real active species (MOOH), significantly improving catalytic performance and material stability.

[0053] According to some embodiments of the present invention, acid ions (such as NO3 -) will cause the material to become unstable at high potentials (such as Co-NiNH / NF or Cu-NiNH / NF) because the acid ions may corrode the material in long-term reactions. In addition, the distribution of acid ions is difficult to be completely uniform, which may lead to uneven electrochemical activity of different active sites and unstable catalytic effect. In the Fe-NiNH / NF system, iron has a low affinity for NO3 - The distribution of ions has a good regulating effect, ensuring the uniformity of acid ions and reducing corrosiveness. At the same time, the stable network structure formed after iron doping can further alleviate the NO3 - The material corrosion caused by the catalyst is effectively improved.

[0054] According to some embodiments of the present invention, after the introduction of multi-metal doping, the interaction between different metals may lead to the problem of unstable electron transfer, and even electronic competition between metals may occur, reducing the transmission efficiency of electrons, thereby affecting the catalytic effect (such as Co-NiNH / NF or Cu-NiNH / NF). Especially under OER reaction conditions, high potential may cause the gradual dissolution or precipitation of doped metal ions, weakening the structural stability of the catalyst. By rationally doping with iron, the electronic configuration of the Fe-NiNH / NF system achieves the optimal state, and the electron distribution is relatively uniform, which effectively alleviates the problem of electronic competition between multiple metals, thereby enhancing stability and activity.

[0055] The following is a further detailed description of a method for preparing a basic nitrate catalyst according to an embodiment of the present invention. According to an embodiment of the present invention, the method comprises:

[0056] S100: Pretreatment of Nickel Foam (NF)

[0057] First, the nickel foam is cut into appropriate sizes, and then ultrasonically cleaned in ethanol, 3M HCl solution, and deionized water for 5-15 minutes respectively; then cleaned with ethanol; and finally dried. The pretreatment of the nickel foam is completed.

[0058] In this step, the nickel foam substrate is ultrasonically and acid-washed to remove surface impurities and increase surface activity, thereby improving the adhesion and dispersibility of the basic metal salt on the nickel foam. Although this step is common, it is the key basis for ensuring the uniform structure and optimized performance of the final product in the present invention.

[0059] According to some embodiments of the present invention, the shape and size of the nickel foam can be adjusted according to actual needs. In the embodiment of the present application, the nickel foam is cut into 2×4×0.15 cm 3 .

[0060] S200: Hydrothermal reaction

[0061] In this step, Ni(NO3)2 is mixed with NaOH or anhydrous ethanol solution and reacted in a hydrothermal reactor, and different metal nitrate solutions (such as Fe, Co, Cu) are added for hydrothermal reaction to obtain a multi-metal synergistic basic salt composite catalyst.

[0062] This process involves two different aspects. The first is the hydrothermal loading of multi-metal basic salts: Ni(NO3)2 is mixed with NaOH or anhydrous ethanol solution and reacted in a hydrothermal reactor to form a basic nitrate layer with different doped metals. This process uses different metal nitrates as precursors, combined with anhydrous ethanol or an alkaline environment, to make the metals evenly deposited on the surface of nickel foam. The hydrothermal method ensures uniform loading under low temperature and low pressure, and is the most innovative and technically advantageous step of the present invention. The second is multi-metal synergistic doping: during the preparation process, different metal nitrate solutions (such as Fe, Co, Cu) are used for hydrothermal reaction to obtain a multi-metal synergistic basic salt composite catalyst. This process controls key parameters such as the proportion of doped metals, environment (ethanol or water), temperature and time, and achieves the optimization of catalytic performance.

[0063] According to some embodiments of the present invention, the hydrothermal loading of multi-metal basic salts and the coordinated doping of multi-metals are achieved by a one-step hydrothermal method, whereas conventional methods may require multiple steps, such as preparing different precursors separately or performing multiple heat treatments, which are more complex.

[0064] According to some embodiments of the present invention, the hydrothermal reaction carried out at 120° C. only takes 6-12 hours to prepare a catalyst with uniform structure and stable performance, avoiding long-term heat treatment and repeated treatment processes, and improving the rapid responsiveness of the entire process.

[0065] S300: Post-cleaning and drying

[0066] In this step, the synthesized samples were washed with deionized water and ethanol and dried in a vacuum oven at 60 °C overnight.

[0067] According to some embodiments of the present invention, in this step, the purity of the material is ensured, and the traditional high-temperature calcination step is avoided, thereby ensuring the integrity of the material structure.

[0068] In combination with some embodiments of the present invention, the present invention adopts a simplified hydrothermal process, which has the following beneficial effects:

[0069] Beneficial effect 1: Simplified process flow. The steps are streamlined and integrated to avoid complicated pre-treatment and post-treatment steps, making the entire preparation process more efficient and easy to control. For example, compared with the traditional multi-step process, the hydrothermal preparation process of the present invention directly completes the processes of precursor dissolution, metal doping, material growth, etc. at one time, reducing the intermediate processing steps, thereby significantly simplifying the process flow and reducing the strict requirements for experimental conditions.

[0070] Beneficial effect 2: shortening the process time. The method of the present invention controls the reaction time of each step within a few hours, greatly shortening the total process time and improving production efficiency. For example, the hydrothermal reaction at 120°C in the step only takes 6-12 hours to prepare a catalyst with uniform structure and stable performance, avoiding long-term heat treatment and repeated treatment processes, and improving the rapid responsiveness of the entire process.

[0071] Beneficial effect 3: Improve the uniform distribution of materials. During the preparation process, by optimizing the hydrothermal reaction conditions, the uniform distribution of metal elements (such as Fe, Co, Cu, etc.) is achieved, ensuring the uniformity of the material components. For example, by reasonably controlling the concentration, temperature, and time of the reactants in the steps, different metals are uniformly deposited on the nickel foam substrate to form a stable multi-metal composite layer, ensuring the uniform distribution of the material, which lays the foundation for the stability of the catalytic performance.

[0072] Beneficial effect 4: Optimizing the pore structure of the material. The hydrothermal method of the present invention generates a porous nanosheet structure, which significantly increases the specific surface area and the number of active sites of the catalyst, and effectively promotes the contact between the electrolyte and the catalyst. For example, during the hydrothermal reaction, due to the synergistic effect of acid ions and doped metals, a uniformly distributed porous structure is naturally formed, which makes the catalyst have excellent oxygen evolution reaction (OER) activity. The porous structure not only improves the catalytic efficiency of the material, but also increases the stability of the reaction.

[0073] Beneficial effect 5: Improve the repeatability and consistency of prepared materials. The simplified hydrothermal process of the present invention has strong controllability in reaction conditions (temperature, reaction time, etc.), making the repeatability of materials between different batches higher and facilitating large-scale production. For example, by strictly controlling the reaction temperature and time in the hydrothermal reactor, the prepared materials have high consistency between different batches, ensuring the stability and controllability of material properties, and are suitable for industrial mass production.

[0074] Beneficial effect 6: Reduced requirements for equipment and environment. Since the present invention uses a low-temperature hydrothermal method to prepare materials, high-temperature calcination and complex post-processing are avoided, equipment requirements and energy consumption are reduced, and it is more environmentally friendly. For example, the hydrothermal method of the present invention has a low reaction temperature and does not require a high-pressure environment, reducing dependence on equipment. The simplified process and low-energy consumption process significantly reduce the requirements for experimental conditions, and have good operability and environmental protection.

[0075] Beneficial effect 7: Reduced material costs. The present invention uses low-cost nickel foam and common metal precursors (such as Ni(NO3)2, Fe(NO3)3, etc.), avoiding expensive precious metals and making the catalyst more cost-effective. For example: using cheap nickel foam as a substrate, introducing transition metals such as Fe, Co, and Cu by hydrothermal method, which not only ensures the efficient electrocatalytic performance of the material, but also significantly reduces the cost of raw materials and preparation, which is conducive to promotion and application.

[0076] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0077] Example 1: Preparation of Fe-NiNH / NF Catalytic Layer by Introducing the Second Metal Fe

[0078] (1) Pretreatment of nickel foam (NF) substrate: Cut the nickel foam into 2×4×0.15 cm 3 ; Ultrasonic cleaning was performed in ethanol, 3M HCl solution, and deionized water (10 minutes for each step), and then cleaned with ethanol to ensure that no impurities remained on the surface. The cleaned nickel foam was blown dry with a hair dryer for later use.

[0079] (2) Weigh 4 mmol Ni(NO3)2·6H2O and 1 mmol Fe(NO3)3·9H2O and dissolve them in 30 ml of anhydrous ethanol. Place the solution together with the nickel foam pretreated in step (1) in a hydrothermal reactor and react at 120°C for 12 hours. Wash the synthesized sample with deionized water and ethanol, and dry it in a vacuum oven at 60°C for 12h-18h.

[0080] Example 2: Introduction of Co metal to prepare Co-NiNH / NF catalyst layer

[0081] (1) Pre-treated nickel foam was prepared in the same manner as step (1) in Example 1.

[0082] (2) Weigh 4 mmol Ni(NO3)2·6H2O and 1 mmol Co(NO3)2·6H2O respectively and dissolve them in 30 ml of anhydrous ethanol. Put the solution and the nickel foam pretreated in step (1) into a hydrothermal reactor and react at 120°C for 12 hours. After the reaction, wash the sample with deionized water and ethanol, and then vacuum dry it at 60°C overnight.

[0083] Example 3: Introduction of Cu metal to prepare Cu-NiNH / NF catalyst layer

[0084] (1) Pre-treated nickel foam was prepared in the same manner as step (1) in Example 1.

[0085] (2) Weigh 4 mmol Ni(NO3)2·6H2O and 1 mmol Cu(NO3)2·3H2O respectively and dissolve them in 30 ml of anhydrous ethanol. Put the solution and the nickel foam pretreated in step (1) into a hydrothermal reactor and react at 120°C for 12 hours. After the reaction, wash the sample with deionized water and ethanol, and then vacuum dry it at 60°C overnight.

[0086] Comparative Example 1: Preparation of Ni(OH)2 / NF Catalytic Layer

[0087] The difference between the Ni(OH)2 / NF prepared in this comparative example and the above-mentioned embodiment is that the second metal is not doped. The specific preparation process is as follows:

[0088] (1) Pre-treated nickel foam was prepared in the same manner as step (1) in Example 1.

[0089] (2) Weigh 5 mmol Ni(NO3)2·6H2O and 0.12 g NaOH and dissolve them in 30 ml deionized water. Place the solution together with the nickel foam pretreated in step (1) in a hydrothermal reactor and react at 120°C for 6 hours. After the reaction is completed, wash the synthesized sample with deionized water and ethanol, and then dry it in a vacuum oven at 60°C overnight.

[0090] Comparative Example 2: Preparation of NiNH / NF Catalytic Layer

[0091] The difference between the NiNH / NF prepared in this comparative example and the above-mentioned embodiment is that there is no alkaline substance and the second metal. The specific preparation process is as follows:

[0092] (1) Pre-treated nickel foam was prepared in the same manner as step (1) in Example 1.

[0093] (2) Weigh 5 mmol Ni(NO3)2·6H2O and dissolve it in 30 ml anhydrous ethanol. Place the solution together with the nickel foam pretreated in step (1) in a hydrothermal reactor and react at 120°C for 12 hours. After the reaction is completed, wash the synthesized sample with deionized water and ethanol and dry it in a vacuum oven at 60°C overnight.

[0094] Test Example 1:

[0095] The performance of the catalytic materials prepared in the above examples and comparative examples was tested.

[0096] 1. Figure 1 The following are SEM images of samples of various embodiments and comparative examples.

[0097] like Figure 1 As shown in the figure, Ni(OH)2 / NF presents the morphology of nanosheets. When NO3 is introduced into the material - After the addition of Fe, NiNH / NF is still a uniformly distributed nanosheet array, but the nanosheets are thinner than Ni(OH)2 / NF. After the introduction of Fe, Fe-NiNH / NF still retains the original nanosheet structure, forming an array layer of transition metal hydroxide nanosheets that grow vertically in an interlaced manner. The retention of the nanosheet structure may be beneficial to the OER reaction, while the nanosheet structures of Co-NiNH / NF and Cu-NiNH / NF are destroyed.

[0098] 2. Figure 2 is the XRD spectrum of Ni(OH)2 / NF; Figure 3 XRD diffraction patterns and Raman comparison diagrams of NiNH / NF, Fe-NiNH / NF, Co-NiNH / NF, and Cu-NiNH / NF.

[0099] Depend on Figure 2 It can be seen that the characteristic peaks of Ni(OH)2 / NF match well with the standard card PDF#00-014-0117, confirming the successful synthesis of Ni(OH)2 / NF. Figure 3 As shown in a, for NiNH-based catalysts, after the introduction of Fe and Co, elements with atomic radius larger than Ni, the XRD characteristic peak shifts to a small angle, while the introduction of Cu, an element with atomic radius smaller than Ni, shifts to a high angle, confirming the successful introduction of the second metal into NiNH. Figure 3 b shows the Raman spectrum. The orange area corresponds to the characteristic peak of Ni, and the green area corresponds to NO3 - The characteristic peaks of Ni(OH)2 / NF show that there is no NO3 - The characteristic peak of NiNH-based catalysts also appeared, confirming that the acid ion NO3 -The successful introduction of basic nitrates.

[0100] 3. Figure 4 The XPS diagram of each sample is used to determine the state of each element in the catalyst.

[0101] To further understand the elemental state of the catalyst, we performed XPS tests. Figure 4 As can be seen, NO3 - The characteristic peak appears at 406.8 eV in the N1s spectrum (reference ZHOUY-N, LI FT, DONG B, et al. Double self-reinforced coordination modulation constructing stable Ni 4+ forwater oxidation[J]. Energy Environ Sci, 2024, 17(4):1468-81.) In addition, Fe in M-NiNH / NF was also detected (Reference ZHANG L, CAI W, BAO N, et al. Implanting an electron donor to enlarge the d–p hybridization of high-entropy(oxy)hydroxide: Anovel design to boost oxygen evolution[J]. Adv Mater, 2022, 34(26): 2110511.) Co (reference GU K, ZHUX, WANG D, et al. Ultrathin defective high-entropy layered double hydroxides for electrochemical water oxidation [J]. J Energy Chem, 2021, 60: 121-6.), Cu (ZHANG L, CAI W, BAO N, et al. Implanting an electron donor to enlarge the d–phybridization of high-entropy(oxy)hydroxide:A novel design to boost oxygen evolution[J]. Adv Mater, 2022, 34(26): 2110511.), which once again confirmed the successful introduction of the second metal element.

[0102] Test Example 2:

[0103] The electrode materials in the embodiments and comparative examples were tested for performance as follows:

[0104] Electrochemical tests were carried out on an electrochemical workstation. The prepared material was used as the anode, the carbon rod as the counter electrode, and Hg / HgO as the reference electrode. The linear sweep voltammetry (LSV) curve of the anode electrode material was measured in 1 M KOH and 1 M KOH + 0.5 M NaCl solutions, respectively.

[0105] The test results are shown in Table 1 and Figure 5 As shown:

[0106] Table 1. Electrocatalytic hydrogen evolution performance data of materials in different embodiments and comparative examples

[0107]

[0108] As shown in Table 1 and Figure 5 As shown, compared with the comparative example, the materials prepared in Examples 1 to 3 exhibited excellent OER performance under both 1 mol / L KOH and alkaline simulated seawater (1 mol / L KOH + 0.5 mol / L NaCl). Specifically, under 1 mol / L KOH, the current density of the materials in Examples 1 to 3 was significantly higher than that of the comparative example, and the starting potential and 100 mA cm -2 The corresponding overpotentials are significantly lower than those of the comparative examples, indicating that the doping elements can effectively enhance the catalytic activity. Under alkaline simulated seawater (1 mol / L KOH + 0.5 mol / L NaCl) conditions, the materials of Examples 1 to 3 still maintain relatively high catalytic performance, that is, compared with the comparative examples, they have stronger corrosion resistance.

[0109] Among them, the Fe-NiNH / NF prepared in Example 1 has better OER performance under 1M KOH and better corrosion resistance in seawater. Under 1mol / L KOH, the current density of the Fe-NiNH / NF prepared in Example 1 is 100mA cm -2 The corresponding overpotential is 310 mV, which is significantly better than other examples Co-NiNH / NF (360 mV) and Cu-NiNH / NF (380 mV). Under alkaline simulated seawater (1 mol / L KOH + 0.5 mol / L NaCl), the current density of Fe-NiNH / NF is 100 mA cm -2 The corresponding overpotential is 320 mV, which is also significantly better than other examples Co-NiNH / NF (400 mV) and Cu-NiNH / NF (415 mV).

[0110] In order to further study the corrosion resistance of Fe-NiNH / NF, the catalytic performance of Fe-NiNH / NF was investigated under simulated high-salinity corrosion conditions (1 mol / L KOH + 2 mol / L NaCl), with NiNH / NF as the control group. Figure 5 b and Figure 5 As shown in e, the current density of NiNH / NF under 1 mol / L KOH+2 mol / L NaCl is 100 mA cm -2 The corresponding overpotential (445 mV) is higher than that of Fe-NiNH / NF (325 mV), and the catalytic activity of NiNH / NF decreases relatively under 1 mol / LKOH and simulated high salinity corrosion conditions (1 mol / LKOH+2 mol / LNaCl), while the catalytic activity of Fe-NiNH / NF does not change much under 1 mol / LKOH and simulated high salinity corrosion conditions (1 mol / LKOH+2 mol / LNaCl). This indicates that doping with Fe can greatly improve the OER performance of the catalytic material and its corrosion resistance under seawater conditions.

[0111] Compared with the elements Cu and Co doped in other embodiments, Fe in Example 1 has a significant optimization effect on the sheet structure of the material, mainly due to the following four reasons:

[0112] 1) Significantly improved electrocatalytic activity: In the Fe-NiNH / NF structure, the interaction between Fe and Ni makes the generation of redox active sites more favorable, thereby improving the overall catalytic efficiency and showing better OER activity.

[0113] 2) Improve the stability and service life of the material: The Fe-NiNH / NF structure introduces iron into nickel hydroxide (Ni(OH)2) to form a more stable composite structure, which effectively resists dissolution or corrosion problems under high potential during long-term electrocatalysis.

[0114] 3) Enhanced conductivity and improved electrolysis efficiency: The Fe element forms a good charge distribution in the nanosheet structure, which makes the overall conductivity of Fe-NiNH / NF better, thereby ensuring the rapid transmission and transfer of electrons on the surface of the material in the OER reaction and improving the efficiency of water electrolysis.

[0115] 4) Promote the uniform distribution of the lamellar structure and increase the number of active sites: that is, the introduction of Fe stabilizes the distribution of the lamellar structure, making it difficult for the lamellar structure to agglomerate, thereby significantly increasing the specific surface area of ​​the catalyst and exposing more active sites to participate in the catalytic reaction.

[0116] This is the result of the inventors' experience and extensive research. Through the Fe-NiNH / NF catalyst provided by the present invention, Fe and NO3 -They support and complement each other, and have a significant synergistic effect, which not only significantly improves the OER activity of the catalyst, but also greatly enhances its corrosion resistance.

[0117] The OER performance of the Co-NiNH / NF and Cu-NiNH / NF catalysts prepared in Examples 2 and 3 under 1 mol / L KOH and alkaline simulated seawater conditions was significantly better than that of the comparative example materials, but slightly inferior to that of the Fe-NiNH / NF catalyst prepared in Example 1. There are mainly four reasons:

[0118] 1) Reaction interference between doped metals: In Co-NiNH / NF and Cu-NiNH / NF, the catalytic performance is improved after the introduction of multi-metal doping. However, the interaction between different metals may lead to the problem of unstable electron transfer, and even electron competition between metals, which will reduce the electron transmission efficiency and thus affect the catalytic effect. Especially under OER reaction conditions, high potential may cause the gradual dissolution or precipitation of Co and Cu doped metal ions, weakening the structural stability of the catalyst. Under simulated seawater (1mol / LKOH+0.5mol / LNaCl) conditions, the strong corrosiveness of Cl- ions makes this problem more prominent.

[0119] 2) The corrosiveness and unevenness that may be caused by the introduction of acid ions: Acid ions (such as NO3 - ) will cause the material to become unstable at high potentials, because the acid ions may corrode the material in long-term reactions. In addition, the distribution of acid ions is difficult to be completely uniform, which may lead to uneven electrochemical activity of different active sites and unstable catalytic effect. In contrast, Fe in Fe-NiNH / NF is very sensitive to NO3 - The distribution of ions has a good regulating effect, ensuring the uniformity of acid ions and reducing corrosiveness.

[0120] 3) The mechanical strength problem of the nanosheet structure: Although the nanosheet structure increases the specific surface area, it is weak in mechanical strength and is prone to sheet peeling and agglomeration during long-term electrocatalysis, which leads to the loss of active sites and affects the service life of the catalyst.

[0121] 4) Complex multi-metal systems may lead to increased costs: The process of introducing multiple metals and special acid ions may increase the manufacturing cost of the catalyst. In particular, Cu is a relatively scarce metal, and its doping may increase the cost; while Fe is relatively low in cost and has a significant effect in improving catalytic performance, with good economic benefits.

[0122] Test Example 3:

[0123] This test example is a test of the electrochemical performance of the catalyst.

[0124] like Figure 6 As shown in a, Ni(OH)2 / NF at a current density of 100 mA cm -2 438 mV overpotential is required for NiNH / NF, while 100 mA cm-2 can be obtained at an overpotential of 410 mV. -2 Current, NO3 - The introduction of the second metal Co, Cu, and Fe further improved the OER performance of NiNH. Among them, Fe-NiNH / NF showed the highest OER activity, 100 mA cm -2 In addition, Fe-NiNH / NF exhibits the lowest Tafel slope ( Figure 6 b) and minimum charge transfer resistance ( Figure 6 c), indicating that Fe-NiNH / NF has excellent kinetic properties and is conducive to the rapid occurrence of OER. In the stability test lasting up to 100 h, compared with Ni(OH)2 / NF and NiNH / NF, Fe-NiNH / NF showed good stability, and the chronopotentiometry (CP) curve did not show a significant increase during the test time ( Figure 6 f). Thereby increasing the service life of the catalyst.

[0125] In summary, alkaline nitrate Fe-NiNH / NF doped with the second metal Fe was prepared by hydrothermal method. - The introduction of - Furthermore, when the second metal Fe was introduced, the OER performance of NiNH was further improved. In addition, Fe-NiNH / NF showed the lowest Tafel slope and the smallest charge transfer resistance, indicating that Fe-NiNH / NF has excellent kinetic properties and is conducive to the rapid occurrence of OER.

[0126] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

Claims

1. A nickel foam-supported basic nitrate catalytic material, characterized in that: The basic nitrate catalytic material is an active layer of metal basic nitrate compounded on a nickel foam substrate; The metal includes one or more of Ni, Fe, Co and Cu.

2. The basic nitrate catalytic material according to claim 1, characterized in that: The active layer of the basic nitrate catalytic material is one or more of Ni(OH)2, NiNH, Fe-NiNH / NF, Co-NiNH / NF or Cu-NiNH / NF.

3. The basic nitrate catalytic material according to claim 1, characterized in that: The volume ratio of the nickel foam to the metal ions is (0.5-1.2) cm 3 :5mmol.

4. The basic nitrate catalytic material according to any one of claims 1 to 3, characterized in that: When preparing the basic nitrate catalytic material, a Ni precursor compound and a metal nitrate are dissolved in a solvent, foamed nickel is added, and then the catalyst is obtained by a hydrothermal reaction.

5. The basic nitrate catalytic material according to claim 4, characterized in that: The Ni precursor compound is Ni(NO3)2·6H2O; and / or; The metal nitrate is M(NO3) x nH2O; and / or The reaction temperature is 110-130°C; the reaction time is 6-12h; Wherein, M is one or more of Ni, Fe, Co, and Cu; x and n are the stoichiometric numbers of nitrate and crystal water, respectively.

6. The basic nitrate catalytic material according to claim 5, characterized in that: The metal nitrate is Fe(NO3)3·9H2O; and / or; The reaction temperature is 120° C. and the reaction time is 12 h.

7. The basic nitrate catalytic material according to any one of claims 5 to 6, characterized in that: The usage ratio of the Ni precursor compound and the metal nitrate is 4 mmol:1 mmol.

8. A method for preparing a nickel foam-supported basic nitrate catalytic material, characterized in that: The following steps are involved: a) pre-treating nickel foam; b) 4mmol Ni(NO3)2·6H2O and 1mmol M(NO3) x nH2O is dissolved in anhydrous ethanol; the M is represented by Ni, Fe, Co or Cu, and the x and n are the stoichiometric numbers of nitrate and crystal water, respectively; c) adding the pretreated nickel foam to the above solution, transferring it to a hydrothermal reactor, reacting at 110-130° C. for 6-12 hours to obtain a sample; The volume ratio of the nickel foam in step a) to the metal in step b) is (0.5-1.2) cm 3 :5mmol; d) Wash the sample and dry it in vacuum at 50-70°C.

9. Use of the basic nitrate catalytic material according to any one of claims 1 to 7 or the catalytic material prepared by the preparation method according to claim 8 in the field of hydrogen production by anode water electrolysis.

10. The use according to claim 9, characterized in that: The hydrogen production by water electrolysis is hydrogen production by seawater electrolysis.

Citation Information

Patent Citations

  • Oxygen evolution reaction catalyst, preparation, application, electrolysis device and seawater cracking method

    CN112501647A

  • Foamed nickel loaded platinum nanoparticle cobalt salt full-electrolysis water catalytic material and preparation method thereof

    CN113235109A

  • Quaternary metal-based alkaline electrolysis seawater oxygen evolution reaction electrocatalyst and preparation method thereof

    CN114481211A

  • Preparation method and application of Fe-Ni composite oxide supported by foamed nickel

    CN115588749A

  • Alkaline electrolyzed water catalyst as well as preparation method and application thereof

    CN118127547A